Internasionaalregtelike Perspektiewe op Switserland se Betrekkinge met Brittanje, die Z.A.R. en die O.V.S. in die Aanloop tot die Anglo-Boereoorlog: ’n Politieke Dilemma - Raath, A. W. G. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
In the decades preceding the Anglo-Boer War Switzerland maintained international relations with Britain as well as the two Boer Republics. In the second half of the 19th century legal relationships between states were shaped by a strong spirit of positivism. Following the trend of the time Switzerland concluded treaties with Britain and the two Boer Republics. Because of the strong international position of Britain, and the emphasis on state practice rather than abstract principles of justice, Switzerland faced a serious political crisis in determining its policy to the said states. Due to the prevailing political and legal climate in the international arena, Switzerland took the pragmatic decision not to intervene in the conflict in spite of the serious impact of the war on the civil populations of both Boer Republics. This article reflects the complicated position in which Switzerland found itself in the approach to the War and the reasons which inspired Switzerland to decide in favour of a pragmatic position rather than supporting the anti-imperialistc stance of the Boer states.